2015
DOI: 10.1037/ccp0000027
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based cognitive therapy (MBCT) reduces the association between depressive symptoms and suicidal cognitions in patients with a history of suicidal depression.

Abstract: Objective: In patients with a history of suicidal depression, recurrence of depressive symptoms can easily reactivate suicidal thinking. In this study, we investigated whether training in mindfulness, which is aimed at helping patients “decenter” from negative thinking, could help weaken the link between depressive symptoms and suicidal cognitions. Method: Analyses were based on data from a recent randomized controlled trial, in which previously suicidal patients were allocated to mindfulness-based cognitive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 28 publications
(41 reference statements)
2
30
0
2
Order By: Relevance
“…This contributes to decrease experiential avoidance from unpleasant psychological events (as they are simply considered as harmless attentional objects), contributing to decrease suicidal thoughts and acts . Interestingly, it has been shown that training in mindfulness weakens the association between depressive symptoms and suicidal ideation in depressed patients , through decrease in cognitive reactivity and ruminations . Besides, trait mindfulness has been negatively correlated to lability of negative affects, independently of depression and mediated by lower maladaptive coping.…”
Section: Discussionmentioning
confidence: 99%
“…This contributes to decrease experiential avoidance from unpleasant psychological events (as they are simply considered as harmless attentional objects), contributing to decrease suicidal thoughts and acts . Interestingly, it has been shown that training in mindfulness weakens the association between depressive symptoms and suicidal ideation in depressed patients , through decrease in cognitive reactivity and ruminations . Besides, trait mindfulness has been negatively correlated to lability of negative affects, independently of depression and mediated by lower maladaptive coping.…”
Section: Discussionmentioning
confidence: 99%
“…One intervention that holds promise here is mindfulness training. Mindfulness, the process of attending to current experience with awareness and acceptance, has been associated with reduced risk of suicidality in several cross-sectional studies (Anastasiades, Kapoor, Wootten, & Lamis, 2016;Chesin & Jeglic, 2016;Lamis & Dvorak, 2013) and is a key feature of clinical treatments shown to reduce risk for suicidality (e.g., Barnhofer et al, 2015;Linehan et al, 2006). Mindfulness may protect against suicidality by enhancing acceptance of negative thoughts and emotions and facilitating re-engagement with goal-directed activities even in the face of adversity (Garland, Farb, Goldin, & Fredrickson, 2015;Kabat-Zinn, 1992;Williams & Swales, 2004).…”
Section: Mindfulness Intervention Enhances Persistencementioning
confidence: 99%
“…However, a person can experience that emotions can be accepted rather than eliminated through mindfulness and acceptance skills. These may weaken the association between unpleasant emotions and suicidal thinking in vulnerable patients [12]. The present study evidences a reduction in cognitive fusion, as measured by the CFQ.…”
Section: Discussionmentioning
confidence: 69%
“…Experiential acceptance and suicidal ideation were negatively correlated in veterans having received ACT [11]. Training in mindfulness was found to weaken the association between depressive symptomatology and suicidal thinking in patients with a history of suicidal depression [12]. Finally, in an open pilot study, our group has recently reported the feasibility of a 7-sessions weekly ACT program for patients suffering from current suicidal behavior disorder, as per DSM-5 criteria.…”
Section: Introductionmentioning
confidence: 99%